Factors Related to the Incidence of Low Birth Weight (LBW) - Dewi Kelele; Rina Waty Sirait; Yuliana Radja Riwu (Journal of Health and Behavioral Science, 2022)
Low birth weight (LBW) is the main indicator of reproductive health and overall public health. LBW refers to babies whose birth weight is less than 2500 grams and has nothing to do with gestational age. The study aims to determine the factors related with the incidence of LBW in Prof.DR.W.Z Hospital. This research is an analytical survey with a cross-sectional approach. The sample amounted to 99 babies born at Prof.DR.W.Z Johanes Hospital for the period January to December 2019 while the respondents were mothers of babies who were selected using the simple random sampling method. The data analysis used was univariate and bivariate analysis with Chi-Square test. The results showed that the factors associated with LBW were parity (p=0.000), nutritional status (p=0.000), and pregnancy anemia (p=0.000), while the factors not related to LBW were maternal age (p=0.120), mother's education (p=0.370) and mother's occupation (p=0791).